Factors Influencing Sample Size for Internal Audit Evidence Collection in the Public Sector in Kenya - Kamau, Guandaru C.; Kariuki, Samuel N. (IJAME Publication, 2012)
The internal audit department has a role of providing objective assurance and consulting services designed to add value and improve an organization’s operations. In performing this role the internal auditors are required to provide an auditor’s opinion which is supported by sufficient and reliable audit evidence. Since auditors are not in a position to examine 100% of the records and transactions, they are required to sample a few and make conclusions on the basis of the sample selected. The literature suggests several factors which affects the sample size for audit purposes of the internal auditors in the public sector in Kenya. This research collected data from 32 public sector internal auditors. The research carried out simple regression and correlation analysis on the data collected so as to test hypotheses and make conclusions on the factors affecting the sample size for audit purposes of the internal auditors in the public sector in Kenya. The study found out that that materiality of audit issue, type of information available, source of information, degree of risk of misstatement and auditor skills and independence are some of the factors influencing the sample size determination for the purposes of internal audit evidence collection in public sector in Kenya
Keywords: Audit evidence; Internal auditors; Materiality; Sample size